Thyroid dysfunctions in patients with chronic renal failure - Pakhle, Ketan; Parikh, Rushab; Jain, Ashwini; Kashyap, Prashant; Dave, Dhaval; Bhate, Archana (International Journal of Research in Medical Sciences, 2017)
Background: Chronic renal failure (CRF), or end-stage renal disease (ESRD), is a progressive, irreversible deterioration in renal function in which the body’s ability to maintain metabolic and fluid and electrolyte balance fails, resulting in the development of clinical symptoms like uraemia or azotemia. Thyroid hormones have an important role in regulating metabolism, development of the kidney, maintenance of water and electrolyte homeostasis, protein synthesis and influencing other hormone function. Tri-iodothyronine (T3) and thyroxin (T4) are the two main hormones produced by the thyroid. The patients with chronic renal failure often exhibit clinical features and laboratory findings which are indicative of thyroid dysfunction, since, kidney is involved in the metabolism and elimination of TH. Methods: This was a cross sectional single centre descriptive study, including 50 patients of either gender between the age of 45-70 years. Results: Present study found a significant positive correlation between the TSH levels and Zulewski score in patients with CRF. Conclusions: Since there was found to be a correlation between the TSH levels and Zulewski score, the evaluation of symptoms and signs with Zulewski score in addition to thyroid function testing in patients with thyroid dysfunction is essential, since it can be a marker for CRF.